Factors Associated with Blood Ordering and Utilization Consistency in Elective Orthopedic Surgery - Maulydia Maulydia; Praditta Adhi Makayasa; Prananda Surya Airlangga; Mohammad Zaim Chilmi (Indonesian Journal of Anesthesiology and Reanimation, 2026)
Introduction: Blood transfusion is commonly performed during surgeries, and administering transfusion according to the actual needs helps minimize blood waste. Anesthesiologists determine transfusion timing, volume, and target hemoglobin (Hb) level to minimize unnecessary usage of blood. Objective: This study aims to identify factors associated with the consistency between blood ordering and utilization in elective orthopedic surgeries, resulting in improving transfusion effectiveness, enhancing efficiency and supporting clinical decision making in blood management. Methods: A total of 326 patients who underwent elective orthopedic surgery between January and December 2023 were included. Sex, age, hemoglobin (Hb) level, estimated blood loss (EBL), and American Society of Anesthesiologists (ASA) physical status, were evaluated in relation to the consistency between ordered and utilized blood. Results: Most patients were male (59.5%), aged 21-30 years (24.8%), had Hb levels of 11.0-12.9 g/dL (38.0%), EBL < 15% (51.2%), and an ASA physical status of 2 (66.6%). The consistency of whole blood (WB) utilization was 50%, while packed red cell (PRC) utilization was higher at 82.8%. WB utilization consistency was significantly associated with EBL (p=0.013) and ASA physical status (p=0.014), most patients showed more orders than actual usage in patients with EBL < 15% and patients with ASA physical status of 2. PRC utilization was not significantly associated with any patient characteristics. Conclusion: Sex, age, and Hb levels did not affect the consistency between ordered and utilized blood for either WB or PRC. EBL and ASA scores influenced WB but not PRC utilization, with greater inconsistency seen in cases with EBL <15% and ASA score of 2.